1)c3h6+hoh(н+) =c3h7oh-получение
2c3h7oh+2na=2c3h7ona+h2
ch3-ch2-ch2oh+cuo(t) =ch3-ch2-coh+cu+h2o
2)сh3-ch2-ch2-ch2oh + cuo(t) =ch3-ch2-ch2-coh +cu+h2o-получение
ch3-ch2-ch2-coh+h2=ch3-ch2-ch2-ch2oh
ch3-ch2-ch2-coh+ag2o(t) = ch3-ch2-ch2-cooh+2ag
3)2ch3-(ch2)3-cooh+2na=2ch3-(ch2)3-coona+h2
2ch3-(ch2)3-cooh+mgo=(ch3-ch2-ch2-ch2-coo)2mg+h2o
ch3-(ch2)3-cooh+naoh=ch3-(ch2)3-coona+h2o
2ch3-(ch2)3-cooh+na2co3=2ch3-(ch2)3-coona+co2+h2o
4)c2h5oh+ch3-cooh= c2h5-o-co-ch3+h2o
c5h11oh+h-cooh= c5h11-o-co-h +h2o
c7h13oh+c2h5-cooh= c7h13-o-co-c2h5+h2o
c5h11oh+ c5h11-cooh=c5h11-o-co-c5h11+ h2o
x+3=x^2+2x-3 x^2+2x-3>0
x^2+2x-3-x-3=0 x^2+2x-3=0
x^2+x-6=0 x₁+x₂=-2
x₁+x₂=-1 x₁*x₂=-3
x₁*x₂=-6 x₁=-3; x₂=1 => x<-3; x>1
x₁=-3 - не входит в ОДЗ x>1
x₂=2
x=2
log_2(2x-1)-2=log_2(x+2)-log_2(x+1) ОДЗ: 2x-1>0 => x>0.5
log_2(2x-1)-log_2(4)= log_2(x+2)-log_2(x+1) x+2>0 => x>-2 log_2((2x-1)/4)=log((x+2)/(x+1)) x+1>0 => x>-1 (2x-1)/4=(x+2)/(x+1) x>0.5
(2x-1)(x+1)=4(x+2)
2x^2+x-1-4x-8=0
2x^2-3x-9=0
D=(-3)^2-4*2*(-9)=81 √81=9
x₁=3
x₂=-1.5 - не входит в ОДЗ
х=3
log_5(2x^2-x)/log_4(2x+2)=0 ОДЗ: 2x^2-x>0 => x>0.5
log(4)log(2x^2-2)/log(5)log(2x+2)=0 2x+2>0 => x>-1
log(2x^2-x)/log(2x+2)=0
log(2x^2-x)=0
log(2x+2)≠0
2x^2-x=1
2x^2-x-1=0
D=9
x₁=1
x₂=-0.5 - не входит в ОДЗ
x=1
log_2x(x^2+x-2)=1 ОДЗ: 2x>0 => x>0
log_2x(x^2+x-2)=log_2x(2x) x^2+x-2>0
x^2+x-2=2x x^2+x-2=0
x^2-x-2=0 x₁+x₂=-1
x₁+x₂=1 x₁*x₂=-2
x₁*x₂=-2 x₁=-2; x₂=1
x₁=2 x>1
x₂=-1 - не входит в ОДЗ
x=2